PENGENALAN PEMBELAJARAN BERBASIS ISU TERHADAP KEMAMPUAN PEMECAHAN MASALAH SOSIAL SAINS DAN SIKAP SOSIAL SISWA SDN 016 TARAKAN - Mahatir Muhammad; Amrin Amrin; Irlosiana Lencau; Fitri Lestari; Afif Sa'diyah; Fadhlan Muchlas Abrori (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2019)
Abstract: Learning in the classroom especially in Elementary School is lack in recognition of issues, so the students are not mastery problemsolving skill. Based in this, It need to introduce student about issueorientedlearning with socioscientific issues to know the effect thislearning to problem solving skill and social attitude. This research usedquantitative approach, pre-experimental reseach, one group pretestposttestdesign. The results of the implementation of this learning wasgood, and the percentage results increased at each meeting. To measurestudents' problem solving skill and social attitude, the results showeddifference between the values before and after treatment. This showedthe influence of issue based learning on social science issues on problemsolving skills and social attitudes